Variation in the orange (Citrus sinensis L.) prices in Mexico - García-Salazar, José Alberto (2021)
Introduction. Identifying the factors that can increase the orange producer prices, it is important because of the negative effects that a decrease in income can have on agricultural producers. Objective. To determine how the industry demand and the area sowed with oranges affect producer, consumer, and wholesale prices. Materials and methods. A synthetic model of the orange market in Mexico that considered the orange production in irrigated and rainfed areas (rain cycle), the fresh and industrial demand, and different levels of transmission of prices was formulated. The model replicated the average value of the most important variables in the orange market of the years 2014-2016. Results. An increase of 5 % in the consumption of the orange juice producing industry would raise producer prices in irrigated areas and under seasonal conditions by 11,1 and 35,8 % respectively, and would place wholesale prices 31,7 % higher than the base situation. A 5 % decrease in the area of orange harvested would have a 15.2 and 49.1% increase in the producer price in irrigated and seasonal areas, in relation to the base situation. Conclusion. The surface and the industrial demand are control measures which prevent the fall of prices. Due to the importance that the orange production has for the growers, the Government should promote measures to prevent the increase in the orange sowed surface from causing the fall in the price and achieve the commitment of the industry to act through demand in emergency situations, that is to say in the years of supply of orange excess.